Theosis : Patristic Remedy for Evangelical Yearning at the Close of the Modern Age. - Gama, Michael Paul.; Sittser, Gerald L. (Eugene : Wipf and Stock Publishers, 2017)
Evangelicalism is reaching an inflection point. The exodus of millennials from Evangelical churches and the growth of those self-identifying as ""Nones, "" as in ""None of the Above, "" for their church affiliation, is concerning for the movement's future. Evangelical leaders offer mixed responses to this challenge--from circling the wagons to an enthusiastic ""Everything must change!"" posture. Theosis takes a different approach. Seeking to understand Evangelicalism and its origins, this book suggests that Evangelicalism is best understood as the sibling of western, Enlightenment Modernity, which.
Pages:1 to 25; Pages:26 to 50; Pages:51 to 75; Pages:76 to 100; Pages:101 to 125; Pages:126 to 150; Pages:151 to 164.
Print version record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072, 650
Keywords: Salvation; Deification (Christianity); Evangelicalism; RELIGION / Christian Theology / Soteriology; Electronic books